Research Brokers We Use and Abuse while Researching Civil Wars and Their Aftermaths – Methodological Concerns. Issue 2 (3rd April 2019) - Utas, Mats
ABSTRACT: In this practitioners note I want, with a number of cases from my own fieldworks, highlight problems and possibilities of collecting first hand material about conflict with a specific focus on research brokers.